Pengaruh Strategi Kerja Kelompok Berbantuan Media Crossword Puzzle Terhadap Kemampuan Bahasa Jepang SMAN 1 Nusa Penida - Ni Wayan At Pramita Dewi; Putu Dewi Merlyna Yuda Pramesti; Yeni Yeni (Universitas Negeri Padang, 2023)
The goals of this study were to investigate how employing the Crossword Puzzle media-assisted group work strategy affected the Japanese language abilities and motivation of class XI students at SMAN 1 Nusa Penida and to gauge the reactions of the students after they had used the approach. Quantitative research using a Quasi Experimental Design was employed for this study. 198 students from SMAN 1 Nusa Penida's 11th grade comprised the sample for this research. Thirty students from Class XI IBB 1 served as the study's experimental group, while another 30 students from Class XI IBB 2 served as the study's control group. Various forms of testing and surveying were employed to glean the necessary information. The results demonstrated that the experimental class, which was assigned the crossword puzzle media-assisted group work method, outperformed the control class in terms of Japanese language proficiency and motivation. The Sig. (2-Tailed) posttest result of 0.000 < 0.05 from the Independent Sample T-Test hypothesis test provides supporting evidence for this. According on the survey data, pupils who used the Crossword Puzzle medium gave an overall favorable answer of 93.6% in the Strongly Agree/Good/Satisfied/Like category. As a result, we may infer that the method of group work aided by the Crossword Puzzle medium can have a beneficial effect on the development of students' Japanese language competence and motivation.